The influences of social media toward the development of terrorism in Indonesia - Yumitro, Gonda; Kurniawati, Dyah Estu; Abdelsalam, Elfatih Abdullahi; Shukri, Syaza Farhana Mohamad (Jurnal Studi Komunikasi, 2022)
This article analyses the influence of the use of social media among terrorist groups toward the development of terrorism in Indonesia. This research is crucial and interesting because the development of social media could be a prominent tool for a particular person or one group’s existence. Data were collected through literature reviews and studies on social media publications on the issue. The collected data were checked, classified, and analysed by using Nvivo plus 12. Based on the data analysis, it was found that terrorist groups have already used various social media such as Twitter, Facebook, YouTube, Instagram, and WhatsApp to recruit, share their ideologies, and spread their threats towards people. Each activity has its target and steps to strengthen their existences. These groups have implemented artificial intelligence (AI) by arranging the content management strategy for using social media within their groups or collaborating with other terrorist organisations' links. The result of this study could be the consideration of government policies in facing the development of terrorist groups, primarily which exist in social media.